The impact of caesarean scar niche on fertility - a systematic review - M. M van den Tweel; S. van der Struijs; S. Le Cessie; K. E Boers (Journal of Obstetrics and Gynaecology)
Background The trend of increasing caesarean section (CS) rates brings up questions related to subfertility. Research regarding the influence of CS on assisted reproduction techniques (ART) is conflicting. A potential mechanism behind CS-induced subfertility is intra uterine fluid resulting from a caesarean scar defect or niche. The vaginal microbiome has been repeatedly connected to negative ART outcomes, but it is unknown if the microbiome is changed in relation to a niche.Methods This systematic review describes literature investigating the effect of a niche on live birth rates after assisted reproduction. Furthermore, studies investigating a difference in microbial composition in subfertile persons with a niche compared to no niche are evaluated. Pubmed, Embase and Web of Science were searched on March 2023 for comparative studies on both study questions. Inclusion criteria were i.e., English language, human-only studies, availability of the full article and presence of comparative pregnancy data on a niche. The quality of the included studies and their risk of bias were assessed using the Newcastle-Ottawa scale for cohort studies. The results were graphically displayed in a forest plot.Results Six retrospective cohort studies could be included on fertility outcomes, with a total of 1083 persons with a niche and 3987 without a niche. The overall direction of effect shows a negative impact of a niche on the live birth rate (pooled aOR 0.58, 95% CI 0.48-0.69) with low-grade evidence. Three studies comparing the microbiome between persons with and without a CS could be identified.Conclusion There is low-grade evidence to conclude that the presence of a niche reduces live birth rates when compared to persons without a niche. The theory that a caesarean has a negative impact on pregnancy outcomes because of dysbiosis promoted by the niche is interesting, but there is no sufficient literature about this.